Re-polarization of immunosuppressive macrophages to tumor-cytotoxic macrophages by repurposed metabolic drugs. (1st January 2021) - Oyarce, Cesar; Vizcaino-Castro, Ana; Chen, Shipeng; Boerma, Annemarie; Daemen, Toos
ABSTRACT: M2-like tumor-associated macrophages promote tumor progression by establishing an immunosuppressive tumor microenvironment. The phenotype and activity of immunosuppressive macrophages are related to their mitochondrial metabolism. Thus, we studied if drugs targeting mitochondrial metabolic pathways can repolarize macrophages from M2 into an M1-like phenotype or can prevent M0-to-M2 polarization. The drugs selected are clinically approved or in clinical trials and target M2-specific metabolic pathways: fatty acid oxidation (Perhexiline and Trimetazidine), glutaminolysis (CB-839), PPAR activation (HX531), and mitochondrial electron transport chain (VLX-600). Murine bone marrow-derived macrophages were either polarized to M2 using IL-4 in the presence of the drugs or polarized first into M2 and then treated with the drugs in presence of IFN-γ for re-polarization. Targeting both fatty acid oxidation with Perhexiline or the electron transport chain with VLX-600 in the presence of IFN-γ, impaired mitochondrial basal, and maximal respiration and resulted in M2 to M1-like re-polarization (increased iNOS expression, NO production, IL-23, IL-27, and TNF-α secretion), similar to LPS+IFN-γ re-polarization. Moreover, drug-induced macrophage re-polarization resulted in a strong tumor-cytotoxic activity. Furthermore, the polarization of M0- to M2-like macrophages was impaired by CB-839, Trimetazidine, HX531, and Perhexiline, while Hx531 and Perhexiline also reduced MCP-1 secretion. Our results show that by targeting cell metabolism, macrophages could be re-polarized from M2- into an anti-tumoral M1-like phenotype and that M0-to-M2 polarization could be prevented. Overall, this study provides rational for the use of clinically applicable drugs to change an immunosuppressive tumor environment into a pro-inflammatory tumor environment that could support cancer immunotherapies.